2021
DOI: 10.1111/cts.13121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of personal pharmacogenomic testing as an educational tool in the pharmacy curriculum: A nonblinded, randomized controlled trial

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, an extensive literature review was conducted regarding the attitudes, perceptions and intentions of health science students regarding PGx and PM. Prior research revealed that students' attitudes towards PGx and PM application and adoption were related, among other factors, to their level of knowledge, their satisfaction from PM and PGx training and their self-confidence to apply PGx and PM in clinical practice [6,7,[13][14][15][21][22][23].…”
Section: Research Framework Of the Proposed Model On Students' Intent...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an extensive literature review was conducted regarding the attitudes, perceptions and intentions of health science students regarding PGx and PM. Prior research revealed that students' attitudes towards PGx and PM application and adoption were related, among other factors, to their level of knowledge, their satisfaction from PM and PGx training and their self-confidence to apply PGx and PM in clinical practice [6,7,[13][14][15][21][22][23].…”
Section: Research Framework Of the Proposed Model On Students' Intent...mentioning
confidence: 99%
“…Rahma et al (2021) framework also pinpointed that both pharmacists' knowledge and skills, often assessed by self-confidence, were correlated with their attitudes, and altogether affected their intentions to undergo a PGx training in the future [7]. Grace et al (2021) examined the impact of Personal Genomic educational testing (PGET) on student knowledge, comfort, and attitudes related to PGx in US students, and they noticed a simultaneous improvement in comfort with PGx clinical skills, PGx patient education, and attitudes towards PGx for all participants (receiving or not PGET) over the course of the study [22]. These findings are in line with the results of other studies mentioning that students' PGx knowledge is positively correlated with their self-confidence (readiness) and attitudes towards PGx implementation in clinical practice [13,15].…”
Section: Research Framework Of the Proposed Model On Students' Intent...mentioning
confidence: 99%
“…1a). According to recent studies, PGx education is now more regularly incorporated into the curriculum for a majority of healthcare institutions (medical school, nursing school, pharmacy school) across the six continental regions [21,22]. This increase in education is indicative of an increasing acknowledgment of PGx in precision medicine.…”
Section: Healthcare Provider Perspectivementioning
confidence: 99%